1977
DOI: 10.1159/000264912
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Development with Age of Aminopeptidase(s) in Tears of Children and other Mammals

Abstract: Proteolytic enzymes are known to appear in tears only following trauma to the cornea. Aminopeptidases, enzymes involved in the final degradation of proteins to free amino acids, were measured and partially characterized for substrate specificity in normal human and animal tears. In all species tested, aminopeptidase activity was greatest for methionine β-naphthylamide of the various synthetic analogs of N-terminal L-amino acids. The substrate specificities for aminopeptidase(s) in tears for 11 different mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…We have shown that most of the sulphatase activity is in the soluble fi'action of tears, although a 8.6+2.4 (10) 10.4+2.0 (7) 112+37 (10) 116 +47 (7) 13__+4 (10) 11+3 (7) 0.28+0.06(17) 0.28+0.10(11) 32+10 (15) 28+8 (8) 3.0+ 1.3 (10) 3.2+ 1.6 (7) small proportion of the activity is associated with particulate material. Watson (1977) has suggested that a number of tear proteins, including albumin, immunoglobulin G and aminopeptidases, are derived from serum because their levels are unaltered in malnutrition while other tear proteins, such as secretory immunoglobulin A, lysozylne and amylase, which are synthesized at mucosal surfaces, are considerably depressed during malnutrition. We have observed considerable interindividual variation in tear weights, tear protein concentration and enzyme activities, but we have not investigated the physiological basis of this variation.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that most of the sulphatase activity is in the soluble fi'action of tears, although a 8.6+2.4 (10) 10.4+2.0 (7) 112+37 (10) 116 +47 (7) 13__+4 (10) 11+3 (7) 0.28+0.06(17) 0.28+0.10(11) 32+10 (15) 28+8 (8) 3.0+ 1.3 (10) 3.2+ 1.6 (7) small proportion of the activity is associated with particulate material. Watson (1977) has suggested that a number of tear proteins, including albumin, immunoglobulin G and aminopeptidases, are derived from serum because their levels are unaltered in malnutrition while other tear proteins, such as secretory immunoglobulin A, lysozylne and amylase, which are synthesized at mucosal surfaces, are considerably depressed during malnutrition. We have observed considerable interindividual variation in tear weights, tear protein concentration and enzyme activities, but we have not investigated the physiological basis of this variation.…”
Section: Discussionmentioning
confidence: 99%